Molecular diagnosis and haemato-biochemical changes in Anaplasma marginale infected dairy cattle - GANGULY, ANITA; MAHARANA, BISWA RANJAN; GANGULY, INDRAJIT; KUMAR, ANKIT; POTLIYA, SANDEEP; ARORA, DEVAN; BISLA, RANBIR SINGH (The Indian Journal of Animal Sciences, 2018)
The present study was a undertaken to diagnose Anaplasma marginale in naturally infected crossbred cows and to determine its effect on haemato-biochemical profile. Blood samples were collected from animals (200) for detection of the rickettsial organism by direct smear and direct blood PCR based techniques targeting the major surface protein 5 (MSP-5). Direct blood PCR revealed a 382-bp amplified fragment in positive control samples. When random blood samples were screened under light microscope and direct blood PCR method, 7.5% of samples were positive under microscopic examination whereas PCR analysis revealed 10.5% samples positive for A. marginale. The infected group (25) showed significantly decreased levels of TEC, Hb and PCV than healthy control animals. However, differences in the red blood cell indices were non-significant indicating normocytic normochromic anaemia in affected crossbred cattle. Serum samples (25) of infected cows showed significantly higher values of ALT, AST, BUN, creatinine and TBIL than that of healthy control. A significant decrease of TSP and albumin was also recorded in the infected cows compared to healthy control. The standardized PCR method of the present investigation may be useful for rapid and accurate diagnosis of A. marginale in subclinical/carrier animals as the whole blood could be directly used. Haemato-biochemical studies concluded that anaemia and erythrophagocytosis are considered to be the major components of this disease and adversely affect liver and soft tissue of the affected animals.